Vitamin D status and associated genetic polymorphisms in a cohort of UK children with non‐alcoholic fatty liver disease. Issue 7 (14th May 2018) - Gibson, P. S.; Quaglia, A.; Dhawan, A.; Wu, H.; Lanham‐New, S.; Hart, K. H.; Fitzpatrick, E.; Moore, J. B.
Summary: Background: Vitamin D deficiency has been associated with non‐alcoholic fatty liver disease (NAFLD). However, the role of polymorphisms determining vitamin D status remains unknown. Objectives: The objectives of this study were to determine in UK children with biopsy‐proven NAFLD (i) their vitamin D status throughout a 12‐month period and (ii) interactions between key vitamin D‐related genetic variants (nicotinamide adenine dinucleotide synthase‐1/dehydrocholesterol reductase‐7, vitamin D receptor, group‐specific component, CYP2R1) and disease severity. Methods: In 103 paediatric patients with NAFLD, serum 25‐hydroxyvitamin D (25OHD) levels and genotypes were determined contemporaneously to liver biopsy and examined in relation to NAFLD activity score and fibrosis stage. Results: Only 19.2% of children had adequate vitamin D status; most had mean 25OHD levels considered deficient (<25 nmol·L −1, 25.5%) or insufficient (<50 nmol·L −1, 55.3%). Patients had significantly lower 25OHD levels in winter months (95% CI: 22.7–31.2 nmol·L −1 ) when compared with spring (30.5–42.1 nmol·L −1 ; P = 0.0089), summer (36.3–47.2 nmol·L −1 ; P < 0.0001) and autumn (34.2–47.5 nmol·L −1 ; P = 0.0003). Polymorphisms in the nicotinamide adenine dinucleotide synthase‐1/dehydrocholesterol reductase‐7 (rs3829251, rs12785878) and vitamin D receptor (rs2228570) genes were independently associated with increased steatosis; while a group‐specific component variant (rs4588) was associated with increased inflammation in liver biopsies. Conclusions: Children with NAFLD in the UK have particularly low winter vitamin D status, with vitamin D insufficiency prevalent throughout the year. Polymorphisms in the vitamin D metabolic pathway are associated with histological severity of paediatric NAFLD.